2014
DOI: 10.1016/j.protcy.2014.10.234
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Physical Activities Using a Smartphone: Evaluation Study Using Multiple Users

Abstract: Nowadays, smartphones play an ubiquitous role in accessing and processing information, most of them having a myriad of integrated sensors that makes them capable of generating information with high accuracy and precision. The monitoring of physical exercises presents itself as one of the new trends, made possible by the use of devices like smartphones. Motion sensors such as the accelerometer enable live motion measurement. This paper intends to study this issue and develop an application for the Android opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Then, the mean velocity of COP displacement was computed [28]. Regarding the pelvic linear acceleration, the smartphone accelerometer signal was low-pass filtered at 10 Hz (4 th -order, zero-phase-lag, Butterworth) [29] and the mean acceleration was calculated as the average of the acceleration magnitude data series [30, 31]. The computation of the COP and acceleration variables was carried out with “ad hoc” software, developed by our research group within LabView 9.0 environment (National Instruments, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Then, the mean velocity of COP displacement was computed [28]. Regarding the pelvic linear acceleration, the smartphone accelerometer signal was low-pass filtered at 10 Hz (4 th -order, zero-phase-lag, Butterworth) [29] and the mean acceleration was calculated as the average of the acceleration magnitude data series [30, 31]. The computation of the COP and acceleration variables was carried out with “ad hoc” software, developed by our research group within LabView 9.0 environment (National Instruments, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The kNN classifier generation is based on the work of Duarte et al [13]. In this research, the authors reached approximately 98% recognition rate by a 1NN classifier with the Euclidean distance metrics.…”
Section: Classificationmentioning
confidence: 94%
“…Previous studies have shown that artificial neural network (ANN), knearest neighbor (kNN) and decision tree (DT) are well applicable for HAR, see for example [5,11,13]. Therefore, to the efficiency measurement of selected features those classifiers have been applied.…”
Section: Classificationmentioning
confidence: 99%
“…Nowadays, smartphones play an ubiquitous role in accessing and processing information, most of them having a myriad of integrated sensors that makes them capable of generating information with high accuracy and precision [28]. Collecting usage information on smartphones is difficult: The collection mechanism itself needs to be built and deployed to a diverse group of participants running a multitude of devices in the wild; data must be collected for extended periods of time to overcome novelty effects and find long-term trends.…”
Section: Conceptual Model Of Context Identification and Prediction Ofmentioning
confidence: 99%